Exploring Multimodality in Teaching Writing: A Narrative Inquiry of an English Teacher in an Indonesian Senior High School - Anjar Nur Cholifah; Doni Alfaruqy; Harits Setyawan (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
Using multimodality in teaching second language writing allows English teachers to creatively combine two or modes in describing what goes on at each stage of the writing process. Studies confirmed that multimodality in teaching English as a foreign language could help to activate classroom atmosphere and inspiring students’ motivation. However, studies focusing on multimodality in teaching writing are still limited. Thus, this study aims at exploring the modes employed by the teacher in teaching writing and investigating how the teacher combined those methods in describing each stage of the writing process. By using narrative inquiry, the researchers obtained the data mainly by using the semi-structured interview. The participant of this study was an English teacher in a high school. The findings stated that a teacher employed modes like visual display, classroom layout, voice quality, gesture, and body movement in teaching writing. The teacher then combined those modes in describing stages of the writing process by designing some activities involving students’ active participation and group work. This study has implications for teachers and researchers interested in exploring multimodality in teaching English particularly in writing and generally in other skills, listening, speaking, and reading.